Microstructure reset-based self-healing method using sub-second electric pulsing for metallic materials. (September 2020) - Jeong, Hye-Jin; Kim, Moon-Jo; Choi, Seung-Jun; Park, Ju-Won; Choi, Howook; Luu, Viet Tien; Hong, Sung-Tae; Han, Heung Nam
Highlights: A novel microstructure reset-based self-healing method for metallic materials is proposed. Sub-second electric pulsing was used to reset the damaged microstructure as a non-autonomous self-healing method. The electric pulsing obviously induced the athermal effect which is different with the thermal effect due to Joule heating. Microstructure resetting-assisted infinite reuse was successfully realized using 301L/316L stainless steels and super-elastic NiTi alloy. This is a new concept combining extreme simplicity, rapidness, and infinite repetition, which cannot be achieved by conventional methods. Graphical abstract: Image, graphical abstract Abstract: Microscale defects in materials damage the originally designed microstructure during their use, degrading their mechanical properties/life expectancy. Therefore, various methods for damage repair in materials have been proposed based on the concept of self-healing. However, self-healing for bulk metallic materials is still a challenge due to their strong atomic bonding. Here, we introduce a sub-second electric pulsing which can enhance the kinetics of microstructural changes to infinitely reset the damaged microstructure of metallic materials as a non-autonomous self-healing method. The principle of microstructure resetting is explained based on three categories of resetting cores: phase transformation, dislocation recovery, and recrystallization. Microstructure resetting assisted infinite reuse is successfully realized using 301L/316L stainless steels and super-elastic NiTi alloy, which are applicable materials of the resetting core. This is a new concept combining extreme simplicity, rapidness, and infinite repetition, which cannot be achieved by conventional methods.